Analisis Yuridis Normatif Terhadap Penyelesaian Sengketa Waris Di Pengadilan Negeri Kota Kediri (Studi Komparasi Jasa Advokad Dan Non Advokad) - Habibah Zulaiha (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
These are designed to identify and test the differences of two groups or more. Studies are conducted to compare a variable, between different subjects and different times and find causal links. Concerning the lawyer as legal aid, or a law service to a community or a client who faces the legal problems that are sorely needed as society grows in awareness of the law and the complexity of legal matters. The purpose of this study is to know the normative juridical analysis on the settling of inheritance disputes district court at Kediri City (lawyer's service comparison study and without lawyer's service). The focus of the problem in this study is that what role uses a lawyer’s service and without the lawyer’s service in the process of ending inheritance at Kediri City district court. What are some obstacles using a lawyer’s service and without a lawyer’s service in the process of ending inheritance at Kediri City district court. The research method uses a normative juridical research. In this method, a consideration of the research specialty includes a descriptive analysis that sets out discussion of the study for obtaining legal certainty associated with a lawyer’s service and without the lawyer’s service with his clients, linked to the rules of law and civil law practice and inheritance. The country with a majority moeslem heir according to Islamic doctrine is also written in section 176-185 of KHI (compilation of Islamic law). Some important items of inheritance are listed in the chapters of this law. An advice for the community, before taking a decision to use the lawyer’s service, the client must be good at choosing the lawyer’s service whether it is according to the procedure or vice versa. If it is understandable and correct so that there are no misconceptions of perception that can hurt the society, for some mistakes of taking a decision using the lawyer’s service.